PENGELOLAAN PENDIDIKAN DAN PEMBELAJARAN BERBASIS POTENSI LOKAL - Husnul Bahri (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Management education and learning have a strategic role in improving human resources as mandated by the ideal of the nation is “the nation”, which was followed by the function of education is to equip humans to be intelligent, skilled, and responsible. A thought that management education study program organized excavated from the needs of the people associated with the local potential that existing resources, evolved from the tradition of local knowledge sector in a particular region. The impact is the effectiveness of education and learning management model based on local potentials can be effectively implemented and effective. To see it is based on a positive response from all parties involved in the activities, and the reaction of the learning outcomes regarding cognitive, affective, and psychomotor